Preoperative Informed Consent: Is It Truly Informed? - SMN Husnain; Z Masood; M Farhan; M Jawaid (Tehran University of Medical Sciences, 2012)
Background: Pre-operative informed consent is an important aspect of surgery, yet there has been no formal training regarding it in Pakistan. This study was done to assess the preoperative informed consent practice. Methods: After taking informed permission, a questionnaire was filled in during an interview with 350 patients, who have undergone elective surgical procedures under routine practice conditions from July to October 2010. All the patients were asked a set of standard questions which related to the information they were provided before the operation as a part of standard informed consent practice. Results: Most i.e. 307 (87.7%) patients were informed about their condition but very few 12 (3.4%) were briefed regarding complications. Only 17 (4.9%) patients said they knew about the risks and complications of proposed anesthesia. One hundred thirty-eight (39.4%) patients said that they were allowed to ask questions while giving consent. Most of the time 196 (56%) consent was taken one day before surgery but in few 2 (0.6%) instances it was taken on the morning of surgery and on operation table in some cases 3 (0.9%) as reported by patients. The consent form was signed by the patients themselves in only 204 (58.3%) cases and by their relatives in the rest. About half the number of patients 171 (48.9%) interviewed were satisfied from the information they received as informed consent process. Conclusion: This study highlights the poor quality of patient knowledge about surgical procedures and the inadequate information provided.